Correction: Network analysis reveals abnormal functional brain circuitry in anxious dogs. - Yangfeng Xu; Emma Christiaen; Sara De Witte; Qinyuan Chen; Kathelijne Peremans; Jimmy H Saunders; Christian Vanhove; Chris Baeken (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0282087.].